The French contribution to the voluntary observing ships network of sea surface salinity. (November 2015) - Alory, G.; Delcroix, T.; Téchiné, P.; Diverrès, D.; Varillon, D.; Cravatte, S.; Gouriou, Y.; Grelet, J.; Jacquin, S.; Kestenare, E.; Maes, C.; Morrow, R.; et al.
Abstract: Sea Surface Salinity (SSS) is an essential climate variable that requires long term in situ observation. The French SSS Observation Service (SSS-OS) manages a network of Voluntary Observing Ships equipped with thermosalinographs (TSG). The network is global though more concentrated in the tropical Pacific and North Atlantic oceanic basins. The acquisition system is autonomous with real time transmission and is regularly serviced at harbor calls. There are distinct real time and delayed time processing chains. Real time processing includes automatic alerts to detect potential instrument problems, in case raw data are outside of climatic limits, and graphical monitoring tools. Delayed time processing relies on a dedicated software for attribution of data quality flags by visual inspection, and correction of TSG time series by comparison with daily water samples and collocated Argo data. A method for optimizing the automatic attribution of quality flags in real time, based on testing different thresholds for data deviation from climatology and retroactively comparing the resulting flags to delayed time flags, is presented. The SSS-OS real time data feed the Coriolis operational oceanography database, while the research-quality delayed time data can be extracted for selected time and geographical ranges through a graphical web interface. Delayed time data have been also combined with other SSS data sources to produce gridded files for the Pacific and Atlantic oceans. A short review of the research activities conducted with such data is given. It includes observation-based process-oriented and climate studies from regional to global scale as well as studies where in situ SSS is used for calibration/validation of models, coral proxies or satellite data. Highlights: The French Sea Surface Salinity observation service is an important component of the global ocean observing system. Procedures for data acquisition on voluntary observing ships, data processing in real and delayed time and data distribution are detailed. A review of research studies based on collected salinity data is presented.